0603 Divided Attention Steering Simulator Compared to Other Daytime Sleepiness Tests in Sleep Apnea. (27th May 2020) - Penzel, T; Henning, S; Glos, M; Huang, Y; Fietze, I
Abstract: Introduction: Sleep apnea is often associated with daytime sleepiness. A test which may be similar to driving situations is the divided attention steering Simulator (DASS) as a surrogate for testing sleepiness at the wheel. In this study we compared DASS parameters against Epworth sleepiness score (ESS) and psychomotor vigilance test (PVT) in subjects with sleep apnea. Methods: In 16 healthy subjects without sleep disorders and in 38 patients with sleep apnea, we tested daytime sleepiness and Performance using different methodologies. We applied the DASS twice, the PVT twice, the testbattery for attentional Performance (TAP), and the MSLT during one day after polysomnography. Results: Sleep apnea patients had a longer response time according to DASS (p<0.05) and a larger average deviation from midline of the road (p<0.05) and left the road more frequently (p<0.05). Response time in DASS correlated well with PVT (p<0.001). We found no significant association between ESS and DASS parameters. We no correlation between MSLT sleep latency and DASS parameters. Conclusion: The DASS is very well to mirror reaction time as determined by PVT. However, the DASS does not reflect sleepiness as determined by MSLT or ESS. The study confirms the finding that reaction time testing, even using different tools, does not relate very well with perceived subjective sleepiness by ESS nor by objective sleepiness as assessed by multiple sleep latency test. Different measures do form a complex Picture which might lead to falling asleep when driving. All tests do show some limitations regarding this assessment. Support: This study was supported by Charite University funds.